Stigma toward mental illness among higher secondary school teachers in Puducherry, South India - Venkataraman, Surendran (J Family Med Prim Care, 2019)
BACKGROUND: A majority of mental illness start during adolescent period, and teachers can be a major resource in provision of mental health services to them. Stigma is a major barrier between persons with mental illness and opportunities to recover. MATERIALS AND METHODS: Cross-sectional analytical study was conducted to assess the stigma toward mental illness and associated factors among higher secondary school teachers in Puducherry from April 2017 to March 2018. Multistage sampling was used to select 566 teachers from 46 schools. A part of the vignette-based “Mental Health Literacy Scale” portraying depression was used to assess stigma toward mental illness. Sociodemographic and work characteristics were also obtained. Data were analyzed using SPSS v16. To identify factors associated with stigma, bivariate analysis was done using Chi-square test and multivariate analysis using logistic regression. RESULTS: Among the teachers, 72.9% and 65.7% showed overall agreement to personal and perceived stigma, respectively, toward case in vignette. Teachers in lower age group [adjusted odds ratio (AOR): 4.6 (95% confidence interval (CI): 2.54–8.33)], male gender [AOR: 2.79 (95% CI: 1.85–4.24)], working in urban [AOR: 2.8 (95% CI: 1.91–4.15)], private schools [AOR: 2.58 (95% CI: 1.77–3.77)], and less teaching experience [AOR: 3.72 (95% CI: 2.4–5.88)] had significantly higher personal stigma. Similarly, lower age group [AOR: 4.6 (95% CI: 2.54–8.33)], male gender [AOR: 2.79 (95% CI: 1.85–4.24)], working in urban [AOR: 2.8 (95% CI: 1.91–4.15)] schools, and less teaching experience [AOR: 3.72 (95% CI: 2.4–5.88)] had significantly higher perceived stigma. CONCLUSION: About 70% teachers showed overall agreement to stigma toward the depressive case vignette. The significant factors influencing stigma were identified. This can act as a baseline to implementmental health training program for teachers therefore bringing an attitudinal shift to being positive toward the psychologically disturbed.